Increasing Parental Participation Trough Marketing Strategi in Early Childhood Education - Moh Agus Sifa'; Nurul Novitasari (Universitas Al-Hikmah Indonesia, 2025)
Early Childhood Education (PAUD) plays a strategic role in shaping children’s early development, with parental involvement serving as a critical determinant of program effectiveness. This study examines the marketing strategies employed by TK Al Hikmah Muslimat NU Tuban to enhance parental participation in early childhood education. The findings indicate that clear market segmentation, positioning based on Islamic values, and consistent communication through digital platforms contribute positively to parental engagement in school activities. Despite these strengths, parental participation remains constrained by time limitations and persistent perceptions of parents as passive recipients rather than active educational partners. This study highlights the importance of developing flexible and interactive partnership models supported by digital communication to foster sustainable parental involvement. The findings offer practical insights for PAUD institutions seeking to strengthen parent–school partnerships through strategic marketing approaches.